DAMPAK KONFLIK MILITER CHINA – TAIWAN TERHADAP PEREKONOMIAN INDONESIA - DANO, DIMASTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
This research aims to determine the impact of the China – Taiwan military conflict on the Indonesian economy. This research on the impact of the China – Taiwan conflict on the Indonesian economy is research using a descriptive qualitative approach. Qualitative studies are literature studies using books and literature as references. The China – Taiwan military conflict includes blockading the Taiwan Strait to hamper Taiwan's economic activities. On the other hand, the United States and its allies will defend Taiwan by retaliating, including by blockading the Malacca Strait, to block China's trade routes, including blocking China's energy imports, most of which go through the Malacca Strait. Amid increasing trade between Indonesia and China and Taiwan, the blockade of sea routes is expected to harm Indonesia's trade with China and Taiwan, including due to an increase in the price of goods caused by disruptions in supply which can cause an increase in the price of goods imported from China, ultimately hurting Indonesian consumers and inflation. This could also affect Indonesia's manufacturing sector which relies on imports of raw materials from China. Economic uncertainty, including creating global economic uncertainty can affect Indonesian financial markets, currency exchange rates, and foreign investment. Investors may become careful in investing their capital in Indonesia. The geopolitical impact of the China-US conflict over Taiwan will encourage the United States to update its alliance structure in the Asia-Pacific to involve more Asian countries in partnership with China. Eventually, military and political competition will have an impact on the economic sector. ABSTRAKTujuan penelitian ini adalah untuk mengetahui dampak konflik militer China – Taiwan terhadap perekonomian Indonesia. Penelitian Dampak Konflik China – Taiwan terhadap Perekonomian Indonesia ini merupakan penelitian dengan pendekatan kualitatif deskriptif. Studi kualitatif merupakan studi kepustakaan dengan menggunakan buku dan literatur sebagai rujukannya. Konflik militer China – Taiwan diantaranya dilakukan dengan memblokade Selat Taiwan dengan tujuan menghambat kegiatan ekonomi Taiwan. Dilain pihak Amerika Serikat dan sekutunya akan membela Taiwan dengan membalas diantaranya dengan cara memblokade Selat Malaka, dengan tujuan untuk menghambat jalur perdagangan China, diantaranya menghambat impor energi China yang mencapai 80% diantaranya dikirim melalui Selat Malaka. Ditengah peningkatan perdagangan antara Indonesia dengan China dan Taiwan, blokade jalur laut, diperkirakan akan merugikan perdagangan Indonesia dengan China dan Taiwan, diantaranya diakibatkan oleh ; kenaikan harga barang yang disebabkan oleh gangguan dalam pasokan yang dapat menyebabkan kenaikan harga barang-barang yang diimpor dari China, pada akhirnya berdampak negatif pada konsumen Indonesia dan inflasi. Ini juga dapat mempengaruhi sektor manufaktur Indonesia yang mengandalkan impor bahan baku dari China. Ketidak pastian ekonomi, meliputi menciptakan ketidakpastian ekonomi global yang dapat mempengaruhi pasar keuangan Indonesia, nilai tukar mata uang, dan investasi asing. Investor mungkin menjadi hati-hati dalam menanamkan modalnya di Indonesia. Dampak geopolitik, konflik China-AS mengenai Taiwan akan mendorong Amerika Serikat untuk memperbarui struktur aliansinya di Asia-Pasifik untuk melibatkan lebih banyak negara Asia bermitra melawan China. Pada akhirnya, persaingan militer dan politik pasti akan berdampak pada bidang ekonomi